Above and Beyond Robotic Surgery and 3D Modelling in Paediatric Cancer Surgery - Privitera, Laura; Paraboschi, Irene; Cross, Kate; Giuliani, Stefano (Frontiers in Pediatrics, 2021)
Technology and innovation are finally shaping a new way to perform cancer surgery. In the next decade, surgeons will need to be ready to adopt novel devices and intraoperative techniques, facilitating more radical tumour resection with fewer complications. The question is if paediatric surgeons are prepared for this sudden leap forward after many decades of unchanged practice. Paediatric surgeons are still underutilising robotic surgery and augmented reality which have been adopted more quickly in adult surgery. We believe it is crucial to support paediatric cancer surgeons to familiarise themselves with a range of novel technologies, possibly reaching clinical practice shortly. This mini-review will focus on novel technologies and devices other than robotic surgery and 3D anatomical modelling.